MODELLING AND RESOURCES CALCULATION OF COAL DEPOSIT IN FIELD X, NUNUKAN REGENCY, EAST KALIMANTAN - MENDE (NIM : 121 04 068); Pembimbing : Dr. Eng, Syafrizal, ST,. MT., OKTAFIANTO
Modelling and calculation of the coal resource is an important step in a series of mining industry. In this phase, the expected outcome is a model coal distribution and an accurate amount of coal resources, which can provide benefits after further investigation. The study was conducted in exploration block owned by PT. XYZ in Nunukan Regency, East Kalimantan. The execution model using a modeling software package, while the resource calculation is done manually by using the polygon method. Then the resource calculation using the program package of resources mentioned above is done as a comparison. From the results of correlation known to have 11 (eleven) of coal seams in the study area. Based on the quantitative requirements of the layer thickness of coal and impurities, then the modeling can be performed on all the seams. The result shows coal seam has a position generally N26 ° E/14 ° and there are 5 (five) faults in the study area. All the faults are normal fault. By using the polygon method, the amount of coal resources contained in the study area amounted to 5,724,899.03 tons of measured resource, 3,729,987.25 tons of indicated resources to and 3,261,663.77 tons of inferred resources. While the results of calculations using the modeling program package provides the results of 3,206,475.48 tons of measured resource, 1,664,999.05 tons of indicated resources and 1,168,958.44 tons of inferred resources.